VEGETATION COMPOSITION ON ECOLOGICAL FUNCTION IN MATARAM MERAH PARK, JAKARTA - Nur Intan Mangunsong; Rini Fitri; Qurrotu Aini Besila (Universitas Medan Area, 2021)
The existence of the city park is important for Jakarta as a metropolitan city with the current activity level of motor vehicles and air pollution greatly affects the quality of the city environment. The selection of vegetation in Mataram Merah park considered functional aspects and aesthetic values . The objective of this study were to determine the composition and type of vegetation landscape in Mataram Merah park and to determine the function of each type of landscape vegetation in Mataram Merah park. This study used a descriptive qualitative method with several stages, which is survey; identification of the name and type of vegetation; size identification; identification of the type of vegetation making up the composition (name of type and size that makes up the vegetation structure). The results showed that Mataram Merah park was generally planted with vegetation that functioned aesthetically rather than functionally. The function of landscape plants in Mataram Merah park were as aesthetics is 96.55%, as controlling view as much as 13.80%, vegetation function as physical barrier as much as 62.07%, plants as controlling erosion 51.72%, function of plants as controlling climate 13.79% and vegetation function for wildlife as much as 17.24%.